Probing molecule-like isolated octahedra via—phase stabilization of zero-dimensional cesium lead halide nanocrystals. Issue 1 (December 2018) - Arunkumar, Paulraj; Cho, Han; Gil, Kyeong; Unithrattil, Sanjith; Kim, Yoon; Im, Won
Abstract Zero-dimensional (0D) inorganic perovskites have recently emerged as an interesting class of material owing to their intrinsic Pb2+ emission, polaron formation, and large exciton binding energy. They have a unique quantum-confined structure, originating from the complete isolation of octahedra exhibiting single-molecule behavior. Herein, we probe the optical behavior of single-molecule-like isolated octahedra in 0D Cesium lead halide (Cs4 PbX6, X = Cl, Br/Cl, Br) nanocrystals through isovalent manganese doping at lead sites. The incorporation of manganese induced phase stabilization of 0D Cs4 PbX6 over CsPbX3 by lowering the symmetry of PbX6 via enhanced octahedral distortion. This approach enables the synthesis of CsPbX3 free Cs4 PbX6 nanocrystals. A high photoluminescence quantum yield for manganese emission was obtained in colloidal (29%) and solid (21%, powder) forms. These performances can be attributed to structure-induced confinement effects, which enhance the energy transfer from localized host exciton states to Mn2+ dopant within the isolated octahedra. Zero-dimensional cesium lead halides show interesting optoelectronic properties owing to the isolated octahedral structure, but their interaction with alien atoms remain elusive. Herein, Arunkumar et al. report manganese ion doping which leads to phase stabilization and higher quantum yield.